Yüksek hassasiyetle bir biyomolekülün ortogonal metotlarının tasarımı ve tayin sınırlarının sayısal analizi - Şahinkaya, Elif (My University, 2025)
Orijinal referans ürünü olarak da bilinen referans ürün, analitik metot geliştirme ve validasyon çalışması için çalışmada kullanılmıştır. Referans ürün spesifikasyonlarını inceledikten sonra spesifikasyonların SEC HPLC sonucunu içerdiğini ancak analitik bir test olarak Protein A kromatografisinin belirtilmediği anlaşılmıştır. Referans ürün spesifikasyonlarına ilişkin bir kayıt olmamasına rağmen, özellikle alt akım üretimi (USP) ve üst akım üretimi (DSP) ürünlerin rutin analizi için alternatif yöntemler gereklidir. Bu çalışmada, Uluslararası Uyumlaştırma Konferansı (ICH M10) tarafından belirlenen kılavuzlara uygun olarak, monoklonal antikorların (mAb) konsantrasyon tayini (titer) validasyonunda ortogonal iki kromatografik yönteminin etkinliği incelenmiştir. SEC HPLC analitik metot validasyon çalışması (0,01 mg/ ml–2,0 mg/ ml) % 1,0 (LLOQ seviyesi) ile % 200,0 aralığında gerçekleştirilmiştir. Protein A kromatografisi analitik yöntemi için (0,0078 mg/ ml–4,0 mg/ ml) % 0,78 (LLOQ seviyesi) ile % 400,0 doğrusallık seviyeleri arasında validasyon çalışması gerçekleştirilmiştir. Monoklonal antikor (mAb) için analitik metot validasyonu, Waters® HPLC ekipmanı, Empower® 3 isimli bir yazılıma sahip PDA dedektörü kullanılarak metotları geliştirilmiş ve valide edilmiştir. Elde edilen kromatogramlar/ datalar proses edilerek istatistiksel analizler (ANOVA) ile doğrulanmıştır. Protein A kromatografisi ve SEC HPLC analitik metotları, ICH M10 kılavuzuna uygun olarak mAb referans ürünü için validasyon parametreleri oluşturularak gerçekleştirilmiştir.

The reference product, also known as the original reference product, was used in the study for bioanalytical method development and method validation study. After reviewing the reference product specifications, it became clear that the specifications included the SEC HPLC result but did not specify Protein A chromatography as an analytical test. Although there is no record of reference product specifications, alternative methods are required, especially for routine analysis of upstream production (USP) and downstream production (DSP) products. In this study, the effectiveness of two orthogonal chromatographic methods in the concentration determination (titer) validation of monoclonal antibodies (mAb) was examined, in accordance with the guideline set by the International Conference on Harmonization (ICH M10). SEC HPLC analytical method validation study (0.01 mg/ ml–2.0 mg/ ml) was performed between 1.0 % (LLOQ level) and 200.0 %. A method validation study was conducted for the Protein A chromatography bioanalytical method (0.0078 mg/ ml–4.0 mg/ ml) between 0.78 % (LLOQ level) and 400.0 % linearity levels. Bioanalytical method validation for monoclonal antibody (mAb) was developed and validated using Waters® HPLC equipment and a PDA detector with software called Empower® 3. The obtained chromatograms/ data were processed and confirmed by statistical analysis (ANOVA). Protein A chromatography and SEC HPLC bioanalytical methods were performed by establishing validation parameters for the mAb reference product in accordance with the ICH M10 guideline.
Design of orthogonal methods for a biomolecule and numerical analysis of the limits of determination
Keywords: Analitik kimya; Analytical chemistry; Chemistry, Analytic; Kimya, Analitik